Disciplining Interdisciplinarity Integration and Implementation Sciences for Researching Complex Real-World Problems - Bammer, Gabriele (ANU Press, 2013)
This book provides collaborative research teams with a systematic approach for addressing complex real-world problems like widespread poverty, global climate change, organised crime, and escalating health care costs. The three core domains are 1. Synthesising disciplinary and stakeholder knowledge, 2. Understanding and managing diverse unknowns, and 3.Providing integrated research support for policy and practice change. Each of these three domains is organised around five questions 1. For what and for whom? 2. Which knowledge, unknowns and aspects of policy or practice? 3. How? 4. Context? 5. Outcome? This simple framework lays the foundations for developing compilations of concepts, methods and case studies about applying systems thinking, scoping and boundary setting, framing, dealing with values, harnessing and managing differences, undertaking dialogue, building models, applying common metrics, accepting unknowns, advocacy, end-user engagement, understanding authorisation, dealing with organisational facilitators and barriers, and much more. The book makes a case for a new research style-integrative applied research-and a new discipline of Integration and Implementation Sciences or I2S. It advocates for progressing these through an I2S Development Drive. It builds on theory and practice-based research in multi-, inter- and transdisciplinarity, post-normal science, systemic intervention, integrated assessment, sustainability science, team science, mode 2, action research and other approaches. The book concludes with 24 commentaries by Simon Bronitt; L. David Brown; Marcel Bursztyn and Maria Beatriz Maury; Lawrence Cram; Ian Elsum; Holly J. Falk-Krzesinski; Fasihuddin; Howard Gadlin and L. Michelle Bennett; Budi Haryanto; Julie Thompson Klein; Ted Lefroy; Catherine Lyall; M. Duane Nellis; Linda Neuhauser; Deborah O'Connell with Damien Farine, Michael O'Connor and Michael Dunlop; Michael O'Rourke; Christian Pohl; Merritt Polk; Alison Ritter; Alice Roughley; Michael Smithson; Daniel Walker; Michael Wesley; and Glenn Withers. These begin a process of appraisal, discussion and debate across diverse networks.